2021
DOI: 10.1177/0032321721993646
|View full text |Cite
|
Sign up to set email alerts
|

Losers’ Consent in Changing Welfare States: Output Dissatisfaction, Experienced Voice and Political Distrust

Abstract: Mature welfare states must increasingly handle growing fiscal pressures and a multitude of needs with smaller resources. Meanwhile, evaluations of policy outputs are characterized as ‘the weakest link’ in welfare state support, resulting in generalized political distrust. We assess the procedural fairness argument that citizens are not only concerned with welfare state outcomes but also assess the fairness of the processes of service delivery. The fairness perspective has usually been tested in cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The results showed that social security satisfaction partially mediated the relationship between social security fairness and overall trust in government including at the central, county, and township levels of government. Previous studies have demonstrated that the fairness of the service delivery process and citizens’ satisfaction with the quality of public services are highly associated with trust in government [ 8 , 58 ]. Our results are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that social security satisfaction partially mediated the relationship between social security fairness and overall trust in government including at the central, county, and township levels of government. Previous studies have demonstrated that the fairness of the service delivery process and citizens’ satisfaction with the quality of public services are highly associated with trust in government [ 8 , 58 ]. Our results are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…While the extent to which citizens accept sortition as a mechanism for representation remains unclear, there is considerable evidence that opportunities for voice tend to increase legitimacy perceptions in the political sphere (e.g. Christensen et al, 2020;De Blok and Kumlin, 2022;Esaiasson et al, 2012) and beyond (Skitka et al, 2003). Citizens may also value that mini-publics provide space for detailed consideration of political issues by citizens with diverse political leanings, thus enabling more considered judgments (Cohen, 1989;Fishkin and Mansbridge, 2017).…”
Section: Expectationsmentioning
confidence: 99%
“…The attribution of benefits versus burdens via policy is a fundamental dividing line in politics. This is true not only for ego-tropic concerns about how an individual's own situation might be either improved or worsened (e.g., Compton & Lipsmeyer, 2019;de Blok & Kumlin, 2022), but also with regard to outgroups that stand to be positively or negatively impacted by a policy (see e.g., Ingram et al, 2007;Bell, 2021). At the same time, "asymmetry" in affectedness-that is, between those who would be negatively or positively affected by a reform-is a longstanding issue in related debates in democratic theory (c.f.…”
Section: Democracy Proportionality and Targeted Representationmentioning
confidence: 99%